2020
DOI: 10.5937/istrped2001050b
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between social exclusion (ostracism) and Internet addiction of adolescent girls

Abstract: This study aims to investigate the relationship between Internet addiction and social exclusion in female adolescents. The relational screening method was used in the study. The sample group of the study consisted of 244 female adolescents aged 12-18 living in Cinar district of Diyarbakir. To determine the exclusion of adolescents in social relations, the Social Exclusion Scale for adolescents has been used as a data collection tool. Besides, Young Internet addiction Short Form developed by Young (1998) which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…First, the results showed that social exclusion positively predicted Internet addiction, as also captured by a limited number of past research (Lim 2019 ; Poon 2018 ). However, in the Turkish sample, while Tas and Öztosun ( 2018 ) came up with a supportive finding, another early research did not report a significant relationship between social exclusion and Internet addiction (Bagir et al 2020 ). The current study is thought to shed light on this controversy both in national and broader contexts.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…First, the results showed that social exclusion positively predicted Internet addiction, as also captured by a limited number of past research (Lim 2019 ; Poon 2018 ). However, in the Turkish sample, while Tas and Öztosun ( 2018 ) came up with a supportive finding, another early research did not report a significant relationship between social exclusion and Internet addiction (Bagir et al 2020 ). The current study is thought to shed light on this controversy both in national and broader contexts.…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, Tas and Öztosun ( 2018 ) concluded the positive predictor role of social exclusion on Internet addiction in a Turkish sample. On the other hand, in another study again with a Turkish sample, no significant association between these two variables was reported (Bagir et al 2020 ). To this end, the present study aims to shed light on the gap and controversy regarding the association between social exclusion and Internet addiction.…”
mentioning
confidence: 87%
“…Individuals with IA are more eager to obtain social satisfaction in the web-based world because their social needs cannot be met in real life. This also causes individuals with IA to rely on the internet and ignore the real world, which has a certain impact on people's daily lives [31]. After leaving the internet, their sense of estrangement in the real world makes people miss the internet more [32], they cannot control their web-based behavior, and they are dominated and occupied by games.…”
Section: Principal Findingsmentioning
confidence: 99%
“…People are excluded by the act of some agent. Areekkuzhiyil (2017)& Bagir et al(2020) identified the several causes of this issue, including lack of education, poverty, unemployment, and social pathologies such as cyber-bullying and domestic abuse (Areekkuzhiyil 2017;Bagir et al 2020).According to Ackah &Udah (2021), the placing of persons on the outskirts of society is the result of entirely new forces. The possession of a communication device, particularly a mobile phoneespecially a smartphoneor a computer with Internet access does not always guarantee social and medial participation.…”
Section: -Theoretical Frame Of the Study: 9-1-social Exclusionmentioning
confidence: 99%
“…It may serve as a reason or justification for social marginalization. As an illustration of cyber-violence phenomena, which may take the form of cyber-bullying, the media is an ideal instrument for both inclusion and exclusion (Areekkuzhiyil 2017; Bagir et al 2020).…”
Section: Teacher Exclusionmentioning
confidence: 99%